Valorization of carob fruit residues for the preparation of novel bi-functional polyphenolic coating for food packaging applications - Goulas, Vlasios; Hadjivasileiou, Loukas; Primikyri, Alexandra; Michael, Christodoulos; Botsaris, George; Tzakos, Andreas G.; Gerothanassis, Ioannis P. (My University, 2019)
The food industry has become interested in the development of innovative biomaterials with antioxidant and antimicrobial properties. Although several biopolymers have been evaluated for food packaging, the use of polyphenolic coatings has been unexplored. The purpose of this work was to develop an antioxidant and antimicrobial coating for food packaging through the polymerization of carob phenolics. At first, the polyphenolic coatings were deposited in glass surfaces polymerizing different concentrations of carob extracts (2 and 4 mg mL−1) at three pH values (7, 8 and 9). Results demonstrated that the coating produced at pH 8 and at a concentration of 4 mg mL−1 had the most potent antioxidant and antimicrobial potential. Then, the coating was applied directly on the salmon fillet (coating) and on the plastic container (active packaging). Peroxide and thiobarbituric acid-reactive substances (TBARS) methods were used to measure the potency to inhibit lipid oxidation in salmon fillets. Furthermore, the anti-Listeria activity of coatings was also assessed. Results showed a significant decrease of lipid oxidation during cold storage of salmon fillets for both treatments; the superiority of applied coating directly on the salmon fillets was also highlighted. Regarding the antimicrobial potency, the polyphenolic coating depleted the growth of Listeria monocytogenes after 10 days storage; while the active packaging had no effect on Listeria monocytogenes. Overall, we describe the use of low-cost carob polyphenols as precursors for the formation of bifunctional coatings with promising applications in food packaging.
Keywords: Antimicrobial activity; Antioxidant activity; Carob fruit; Coating; Polymerization; Polyphenols; Salmon